Relationship between muscle power, muscle volume and limb length in healthy male and female adolescents - Souhail Bchini; Nadhir Hammami; Dhouha Moussaoui; Taoufik Selmi; Najla Mhimdi; Anissa Bouassida; Abderraouf Ben Abderrahman; Ismail Laher; Juan Del Coso; Hassane Zouhal; Hassane Zouhal (Frontiers in Sports and Active Living)
ObjectiveMuscle power is essential for the activities of daily living. Muscle power production depends on numerous factors such as muscle size and length, muscle architecture and fiber type and varies with age during growth. The association between muscle power output during a jump and lower limb muscle volume and length in adolescents is largely unknown. This study determined the relationships between muscle power developed during a countermovement jump with lower limb muscle volume and length in adolescents aged between 16 and 19 years.MethodsForty healthy adolescent males (n = 20) and females (n = 20) aged 16 to 19 years underwent a counter-movement jump (CMJ) test. Muscle power (MP) during the jump was calculated using the Gomez-Bruton equation. Lower limb muscle volume (MV) and length were calculated in both sexes using anthropometric methods. Pearson correlation was used to assess the associations between variables. Independent-sample t-tests were used to compare anthropometric and muscle performance data between males and females. Cohen's d was used to determine the size of the differences.ResultsThere were differences in all anthropometric variables between males and females (p < 0.001). CMJ height (d = 4.45; p = 0.001) and MP (d = 4.74; p = 0.001) were greater in males than in females (p < 0.001). These differences persisted when jump performance was normalized to the MV (d = 1.05; p = 0.01) and length (d = 4.07; p = 0.001). There were correlations between MV and MP for males and females, with a significant correlation between limb length and MP for males (r = 0.55; p = 0.002).ConclusionsThis study indicates that MV and length are associated with MP production during a CMJ in adolescents aged between 16 and 19 years, suggesting that these factors may be important determining factors for vertical jumping performance during adolescence. The sex-differences in jump performance variables persisted after normalization by MV and length, suggesting that MV and length did not entirely explain the sex difference in muscle power output during a CMJ.